Straw-derived biochar mitigates CO2 emission through changes in soil pore structure in a wheat-rice rotation system. (March 2020) - Fan, Ruqin; Zhang, Baohua; Li, Jiangye; Zhang, Zhenhua; Liang, Aizhen
Abstract: To better understand the relationships between soil pore structure features and soil CO2 emission and soil organic carbon (SOC) sequestration following different straw return modes, undisturbed soil cores (0–5 cm and 5–10 cm) were collected from a rice-wheat rotation system under 4 straw return treatments as (1) no straw return (CK), (2) straw direct return (DR), (3) straw biochar return (BR); (4) straw-pig manure fermentation return (FR) for six years. Pore structure parameters including pore size distribution, porosity, connectivity, anisotropy and fractal dimension (FD) were determined using X-ray computer tomography. Soil CO2 flux and concentrations of SOC, readily oxidable carbon and nutrients were also measured. The results showed that BR and FR had significantly higher SOC concentration than DR and CK. Porosity and number of >500 μm and 500-100 μm macropores, FD and connectivity were significantly highest under FR and was lowest under BR. FR and DR produced 28.1%–32.4% higher C–CO2 than CK and BR in wheat growing season, and 9.80%–16.9% higher in rice season. Soil CO2 emission and C concentrations were significantly related to soil pore structure parameters. The CO2 emission was most significantly related to number of >500 μm pores and FD, indicating that poorly developed pore structure under BR hindered the production and diffusion of CO2 from soil. These results enhanced our understanding of the relationship between soil pore structure and CO2 emission following biochar application, and provided evidence for decision making process in choosing proper straw managements to promote SOC sequestration and reduce CO2 emission. Highlights: Soil CO2 flux and SOC were significantly related to soil pore structure parameters. Soil CO2 flux was lower after straw biochar return than raw straw and straw compost. Straw biochar significantly raised concentrations of soil organic C and nutrients. Straw biochar reduced number and porosity of macropores and increased micropores. Straw biochar reduced pore connectivity and fractal dimension and raised anisotropy.